Efeito da aplicação de prostaglandina (PGF2α) no pós-parto imediato sobre a incidência de retenção de placenta em vacas de leite - Santos, R. M. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP]; Souza, A. H. [UNESP]; Meneghetti, M. [UNESP]; Ferreira, N. [UNESP] (FapUNIFESP (SciELO), 2002)
The purpose of this study was to evaluate the effect of an intramuscular injection of prostaglandin, within the first hour post partum, on the incidence of retained fetal membranes in cows, at 8 and 12 hours post-partum. Eighty-two cows were used as controls and 82 were treated with 25mg of prostaglandin (LUTALYSE®, 5ml), in two different farms. Cows treated with PGF 2α released the placenta faster (P < 0.10) than cows in the control group (7.72±0.84 vs. 10.07±1.09h). The incidence of retained placenta with more than 8h post partum was 30.5% in the control group and 17.1% in the treated group (P < 0.05), and with more than 12h was 19.5% in the control group and 12.2% in the treated group (P < 0.10). Farm, body condition score and parity showed influence on retained placenta rates, whereas sex of calf and help during calving did not have influence. These data showed that prostaglandin treatment within the first hour post-partum is capable of reduce the incidence of retained placenta and may work as a preventive treatment.
The effect of Prostaglandin (PGF2α) injection in the early post partum period on the incidence of retained placenta in dairy cows
Keywords: Dairy cow; Prostaglandin; Retained placenta; prostaglandin F2 alpha; prostaglandin F2 alpha trometamol; animal experiment; cattle farming; controlled study; dairy cattle; drug effect; evaluation; female; fetus membrane; hormonal therapy; labor induction; nonhuman; parity; puerperium; retained placenta; species comparison; Animalia; Bos taurus